Colloid clogging of saturated porous media under varying ionic strength and roughness during managed aquifer recharge - Du Xinqiang; Song Yalin; Ye Xueyan; Luo Ran (Journal of Water Reuse and Desalination, 2019)
Column experiments were conducted to examine the clogging effects of colloids under controlled conditions of solution ionic strength (IS) and porous media roughness. The results showed that colloids in recharge water play an important role in the clogging process of saturated porous media, such that even a small amount of colloid may cause a large reduction in the permeability of the porous medium. Clogging at the pore throat was inferred to be the main reason for the severe permeability reduction of porous media. The characteristics of colloid clogging were clearly influenced by both IS and medium roughness. Recharge water with a higher IS facilitated greater attachment of colloids to the surface of the saturated porous medium, which lead to superficial clogging, while collectors with a rough surface resulted in greater clogging than collectors with a smooth surface.